Abalone tales collaborative explorations of sovereignty and identity in native California - Field, Les W. (Narrating native histories., 2008)
Examines the meaning of abalone among past and present California Indian tribes and how these interpretations of its meaning address larger issues of sovereignty and identity within the tribes